Robustness of the Theory of Planned Behavior in Predicting Entrepreneurial Intentions and Actions - Kautonen, Teemu; van Gelderen, Marco; Fink, Matthias (Entrepreneurship Theory and Practice, 2015)
This analysis demonstrates the relevance and robustness of the theory of planned behavior in the prediction of business start–up intentions and subsequent behavior based on longitudinal survey data (2011 and 2012; n = 969) from the adult population in Austria and Finland. By doing so, the study addresses two weaknesses in current research: the limited scope of samples used in the majority of prior studies and the scarcity of investigations studying the translation of entrepreneurial intentions into behavior. The paper discusses conceptual and methodological issues related to studying the intention–behavior relationship and outlines avenues for future research.